Pengaruh Kecerdasan Emosional Dan Kecerdasan Spritual Melalui Komitmen Organisasi Terhadap Kinerja Karyawan Moon Bamboo Canggu - Ayu Suryawati; Surya Nugraha (Journal Research of Management, 2025)
This study aims to analyze the influence of emotional intelligence and spiritual intelligence through organizational commitment on employee performance at Moon Bamboo Canggu. The population of this study was all nurses at Moon Bamboo Canggu. The sampling technique in this study used the probability sampling method totaling 149 people. The research analysis technique was carried out using the Parth analysis approach. The results of the analysis show that 1) emotional intelligence has a positive and significant effect on organizational commitment; 2) Spiritual intelligence has a positive and significant effect on organizational commitment; 3) Emotional intelligence has a positive and significant effect on employee performance; 4) Spiritual intelligence has a positive and significant effect on employee performance; 5) Organizational commitment has a positive and significant effect on employee performance; 6) Emotional intelligence has a positive and significant effect on performance through organizational commitment. Organizational commitment can act as an intervening variable in the relationship between emotional intelligence and employee performance; and 7) Spiritual intelligence has a positive and significant effect on performance through organizational commitment. Organizational commitment can act as an intervening variable in the relationship between spiritual intelligence and employee performance at Moon Bamboo Canggu. It is expected that managers at Moon Bamboo Canggu will be able to maintain and improve emotional intelligence, spiritual intelligence and organizational commitment in an effort to improve employee performance at Moon Bamboo Canggu.